ANTIOXIDANT ACTIVITY OF THE METHANOL EXTRACT OF TURKEY EGGPLANT (Solanum betaceum Cav.) INVITRO - Surya, Alfin; Anggi Wulandari; Hesti Marliza; Zaiyar (LLDIKTI X Sumbar, Riau, Jambi, Kepri, 2024)
Duch Eggplant rich in phytochemicals, such as polyphenols, flavonoids, and carotenoids. Studies have demonstrated the powerful antioxidant activity of these compounds, which can shield body cells from free radical-induced oxidative damage.The aim of this study is to determine the IC50 value of the antioxidant activity present in the skin of the Holland turnip. This study also has implications for human health. Knowing the anti-oxidant skin activity in the inviter allows us to estimate the potential benefits of protecting the body from oxidative damage. 1.1-diphenyl-2-picrylhydrazil (DPPH) is the method employed. This method involves measuring the ability of the extract to neutralize the free radicals in DPPH. We will observe the color changes from purple to yellow and evaluate the free radical's capture capacity based on the degree of color change. The study's findings revealed an IC50 value of 41,019 ppm. The conclusion from the IC50 values obtained is that the methanol extract in the skin of the Dutch teranga has an antioxidant activity that is very strong to counter free radicals.